PENGARUH PENGETAHUAN DAN DUKUNGAN IBU BAYI TERHADAP PEMBERIAN ASI EKSKULUSIF PADA BAYI USIA 0-6 BULAN DI WILAYAH KERJA PUSKESMAS BATANG BERUH KECAMATAN SIDIKALANG KABUPATEN DAIRI - Nurcahaya Nainggolan; Marta Imelda Br Sianturi; Hilda Yani Karo Karoi (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2021)
The low rate of achieving exclusive breastfeeding certainly needs attention because it contributes to the low quality of human resources in the future and also has an impact on high morbidity and mortality rates. However, this is closely related to the not yet optimal exclusive breastfeeding by breastfeeding mothers caused by several factors that affect the success of exclusive breastfeeding. This type of research is observational analytic using cross sectional design. The study population was all mothers who had babies aged 0-6 months in the Working Area of ​​the Batang Beruh Community Health Center, Sidikalang District, Dairi Regency, totaling 345 people. The research sample was 100 people. In this study, primary data was required using questionnaires and secondary data through the Batang Beruh Community Health Center report. The data analysis used was univariate analysis with the frequency distribution of the research variables, bivariate with the chi-square test, and multivariate with the logistic regression test. The results showed that there was an effect of the knowledge of the baby's mother on giving exclusive AS1 to infants aged 0-6 months (p<0.001). There is an effect of practical support (p = <0.001), on exclusive breastfeeding in infants aged 0-6 months. There is an influence of the knowledge of the baby's mother on exclusive breastfeeding in infants aged 0-6 months. There is an influence of the baby's mother's support on exclusive breastfeeding in infants aged 0-6 months